Pengaruh Cara Masak Dan Lama Penyimpanan Nasi Di Suhu Dingin Terhadap Kadar Glukosa: The Effect of Cooking Methods and Cold Storage Duration on the Glucose Content of Rice - Yuli Sulistiawati Sihombing; Eka Farpina; Askur (Depertemen Teknologi Pertanian Universitas Hasanuddin, 2026)
Diabetes mellitus is a global health problem with an increasing prevalence in Indonesia. Excessive rice consumption can affect blood glucose levels. Cooking methods and rice storage are assumed to influence glucose content. This study aimed to determine the effect of cooking methods and cold storage duration on the glucose content of rice. A quasi-experimental method with a pretest-posttest design was applied. The samples consisted of three types of rice cooked using two different methods and stored at 4–8°C with various storage durations. Glucose levels were measured using the Luff Schoorl method, and the data were analyzed with Two Way Anova. The results showed a consistent decrease in glucose levels in all types of rice as storage time increased. White rice cooked with a rice cooker decreased from 8.2965% (0 hours) to 6.8351% (6 hours). Black rice had the lowest glucose content, decreasing from 5.0464% to 3.8959%. Red rice decreased from 6.4572% to 5.2882%. A similar decrease was also observed in rice cooked with a steamer. Statistical analysis showed no significant effect of cooking methods and storage duration on glucose levels (p = 0.996 > 0.05). In conclusion, glucose levels decreased in all three types of rice stored at cold temperatures, with black rice showing the lowest glucose content.